Nonlinearity as an explanation of the forward exchange rate anomaly - Derek Bond; Niall Hession; Michael J. Harrison; Edward J. O'Brien (University College Dublin, UCD School of Economics, 2008)
This paper shows that nonlinearity can provide an explanation for the forward exchange rate anomaly (Fama, 1984). Using sterling-Canadian dollar data, and modelling nonlinearity of unspecified form by means of a random field, we find strong evidence of time-wise nonlinearity and, significantly, obtain parameter estimates that conform with theory to a high degree of precision: the anomaly disappears.
hdl:10197/1272
Keywords: C22; F31; 330; Forward exchange rate anomaly; nonlinearity; random field regression